Intelligent Interconnection of Parallel LCC-HVDC Links and AC Grids for Transient Stability Enhancement under Faults Conditions - Bakdi, Moussa; Taleb, Rachid; Toualbia, Asma; Mellah, Hacene; Mehedi, Fayçal; Bouyakoub, Ismail; Benziane, Madjid Meriem (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2026)
The intelligent interconnection of AC grids across diverse regions, incorporating renewable energy sources and complex, a nonlinear grid configurations, presents significant challenges to power system stability. To mitigate instability and suppress power oscillations during short-circuit faults in AC grids, this work focuses on leveraging high-performance power electronic converters, specifically Line Commutated Converters (LCCs) based on High-Voltage Direct Current (HVDC) in parallel links, to facilitate efficient power exchange and enhance grid integration and stability. This work proposes an advanced control framework for intelligent interconnection systems; a dual-layer control strategy is introduced, combining a Conventional Power System Stabilizer (CPSS) for local damping of synchronous generator oscillations and a Power Oscillation Damping (POD) controller for global mitigation of inter-area and Wide-Area Oscillations (WAO). This integrated approach is established as a leading control methodology for LCC-HVDC systems, enabling robust synchronous interconnections between hybrid AC/DC grids. The paper further examines key challenges in designing and implementing the LCC-HVDC-based POD controller, addressing dynamic performance and system-wide coordination. Dynamic simulations are conducted using the Power System Toolbox (PST) in MATLAB, leveraging its user-friendly interface and computational efficiency. The results demonstrate superior dynamic response, with rapid oscillation damping and enhanced steady-state performance, validating the proposed controller's efficacy in improving transient stability.